What value added in the trade balances of euro area financial centres? - Virginia Di Nino; Anna Ekstam (European Central Bank (ECB), 2020)
Beside large capital flows, euro area financial centres feature important and growing trade surpluses. We investigate the composition of their gross trade flows and disentangle (i) domestic and foreign production content that is (ii) directly traded with final absorbing economies or embedded in intermediates that are carried to final destination by partner countries. This accounting exercise uncovers that foreign production transiting through their borders accounts for most of the surpluses of financial centres but also that the net surplus in domestic value added traded directly with final consumers is twice as large as in other euro area economies. MNEs allocate the value created globally to financial centres. They do so through transfer pricing practices which undermine the correct representation of the external position of these countries with a bearing also on the external position of the euro area. Their participation in production chains also appears oddly large. When we replace the official trade statistics with predictions based on the gravity law of trade, the surpluses of main euro area financial centres disappear.
Keywords: F14; F23; F40; 330; financial centres; profit shifting; trade balance; domestic and foreignvalue added